Pengaruh Kualitas Produk, Harga, dan Suasana Toko Terhadap Minat Pembelian Ulang Konsumen Pada KKV di Wilayah Tangerang dan Tangerang Selatan - Annisa Mu’izztikhomah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research was conducted to determine the influence of product quality, price, store atmosphere on consumer repurchase intention at KKV in the Tangerang and South Tangerang areas. The number of respondents was 88 who were selected through purposive sampling. The research uses the SEM-PLS analysis method with SmartPLS4 software. The results of this research show that product quality, price and store atmosphere have a positive and significant effect on repurchase intention.